2012
DOI: 10.3858/emm.2012.44.4.022
|View full text |Cite
|
Sign up to set email alerts
|

CpG methylation at GATA elements in the regulatory region ofCCR3positively correlates withCCR3transcription

Abstract: DNA methylation may regulate gene expression by restricting the access of transcription factors. We have previously demonstrated that GATA-1 regulates the transcription of the CCR3 gene by dynamically interacting with both positively and negatively acting GATA elements of high affinity binding in the proximal promoter region including exon 1. Exon 1 has three CpG sites, two of which are positioned at the negatively acting GATA elements. We hypothesized that the methylation of these two CpGs sites might preclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The CpG islands of FUT1, FUT2, HEXA, HEX, NAGA, and ST3GAL1 were found to contain 20, 11, 14, 18, 23, and 18 putative TFBSs, respectively. Methylation of TFBSs for SP1, CREB, Myc, USF-1, CTCF, GATA-1, and AP-2 decreases the affinity of protein-DNA interactions, thereby lowering the transcription rate (Clark et al, 1997;Perini et al, 2005;Kim and Leonard, 2007;Uhm et al, 2012). We found SP1 TFBSs in all CpG islands identified in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…The CpG islands of FUT1, FUT2, HEXA, HEX, NAGA, and ST3GAL1 were found to contain 20, 11, 14, 18, 23, and 18 putative TFBSs, respectively. Methylation of TFBSs for SP1, CREB, Myc, USF-1, CTCF, GATA-1, and AP-2 decreases the affinity of protein-DNA interactions, thereby lowering the transcription rate (Clark et al, 1997;Perini et al, 2005;Kim and Leonard, 2007;Uhm et al, 2012). We found SP1 TFBSs in all CpG islands identified in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…Fresh CB CD34 + cells were immunomagnetically purified from human CB mononuclear cells using a MACS CD34 microbead kit (Miltenyi Biotec). These purified cells were then induced to differentiate into eosinophils for 24 or more days, as previously described in detail . Eosinophilic differentiation was monitored on the basis of granule formation and nucleus shape following staining with Diff‐Quick solution.…”
Section: Methodsmentioning
confidence: 99%
“…20 Although an inverse correlation between DNA methylation and gene expression is very well known, the opposite is not yet well understood, although reported in some large-scale studies 54 and highly dependent on the genomic context. [55][56][57] To better understand this unusual relation between DNA methylation and gene expression, we have studied PEAR1 DNA methylation, during early and late megakaryopoiesis. We found that parallel progressive elevation of PEAR1 CGI1 methylation and PEAR1 expression occurs in early differentiation.…”
Section: Discussionmentioning
confidence: 99%